PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB), JUMLAH PENDUDUK, DAN JUMLAH PENDUDUK YANG BEKERJA TERHADAP KETIMPANGAN PENDAPATAN KABUPATEN/KOTA DI PROVINSI JAWA TIMUR PADA TAHUN 2015-2019 - Ramadhan, Nurmandana; Lestari, Veronika Nugraheni Sri; Sukman , JFX Susanto; Handini, Sri (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
East Java Province has different potential in each regional due to the geographical conditions. By reason of potential differences, it effects unequal distribution of income and income inequality. This study aims to determine the effect of Gross Regional Domestic Product (GDP), total population, and number of working population on regency/City income inequality in Eat Java Province in 2015-2019. This study applies quantitative method. The data used in this study is form of secondary data from the cross-section of 38 regencies/cities in East Java Province at the time series started from 2015-2019, the data obtained from Central Statistics Agency of East Java. Panel data is processed using E-views 9 which produces a fixed effect regression model. The result of this study shows that all research variables have a simultaneous effect on income inequality. Partially all independent variables, such as Gross Regional Domestic Product, population, and working population have a significant effect on income inequality.